ANALISIS PEMAHAMAN MAHASISWA TERHADAP PEMBUKTIAN PERNYATAAN MATEMATIIKA PADA TOPIK GRUP DENGAN MODUL BERBASIS LOGIKA PEMBUKTIAN - Defri Ahmad; Fridgo Tasman (Departemen Matematika, 2020)
Abstract- Proving mathematics statement is one of important ability for undergraduate student to learn mathematics, especially in learning abstract algebra, real analysis, linear algebra, etc. More than a half of topic in group need proving ability to be mastered. In this article, students’ understanding on proving some statement related to group (abstract algebra) that has been help by using proof reasoning module is examined. Data of student responses are collected using three item test and interview. Based on the result student ability in starting answer and create proving structure has been improved. But students’ overall score still satisfied because they fail on choose some basic concept like theorem or definition to help them in proof. Keyword- Proof Reasoning, Group, Proof Technique, Statement Type